Snow White with the red hair. 4 - Akiduki, Sorata (Shojo beat manga., 2019)
"Shirayuki is an herbalist famous for her naturally bright-red hair, and the prince of Tanbarun wants her all to himself! Unwilling to become the prince's possession, she seeks shelter in the woods of the neighboring kingdom, where she gains an unlikely ally--the prince of that kingdom! He rescues her from her plight, and thus begins the love story between a lovestruck prince and an unusual herbalist... Shirayuki lays her life on the line to help Kihal and her bird, Popo, prove their worth to the kingdom--which leads Zen to kiss her for the very first time! Now she can't get that kiss out of her head. Will she be able to keep her cool around the man she's falling for?"--Provided by publisher.